A model of longitudinal hemodynamic alterations after mild traumatic brain injury in adolescents. (April 2019) - Thibeault, Corey M; Thorpe, Samuel; Canac, Nicolas; O'Brien, Michael J; Ranjbaran, Mina; Wilk, Seth J; Hamilton, Robert B
There is an unquestionable need for quantitative biomarkers of mild traumatic brain injuries. Something that is particularly true for adolescents – where the recovery from these injuries is still poorly understood. However, within this population, it is clear that the vasculature is distinctly affected by a mild traumatic brain injury. In addition, our group recently demonstrated how that effect appears to show a progression of alterations similar but in contrast to that found in severe traumatic injuries. Through measuring an adolescent population with transcranial Doppler ultrasound during a hypercapnia challenge, multiple phases of hemodynamic dysfunction were suggested. Here, we create a generalized model of the hemodynamic responses by fitting a set of inverse models to the dominant features from that work. The resulting model helps define the multiple phases of hemodynamic recovery after a mild traumatic brain injury. This can eventually be generalized, potentially providing a diagnostic tool for clinicians tracking patient's recovery, and ultimately, resulting in more informed decisions and better outcomes.